1993
DOI: 10.1111/j.1471-4159.1993.tb05835.x
|View full text |Cite
|
Sign up to set email alerts
|

Subtypes of Sodium‐Dependent High‐Affinity L‐[3H]Glutamate Transport Activity: Pharmacologic Specificity and Regulation by Sodium and Potassium

Abstract: Some data suggest that the sodium-dependent, high-affinity L-glutamate (Glu) transport sites in forebrain are different from those in cerebellum. In the present study, sodium-dependent transport of L-[3H]Glu was characterized in cerebellum and cortex. In both cerebellar and cortical tissue, activity was enriched in synaptosomes. Approximately 100 excitatory amino acid analogues were tested as potential inhibitors of transport activity. Many of the compounds tested inhibited transport activity by < 65% at 1 mM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(64 citation statements)
references
References 59 publications
4
60
0
Order By: Relevance
“…Our results show that (lS,3R)-ACPD, a mGluR agonist acting on multiple subtypes, stimulates PLD activity in adult rat hippocampal, neocortical and striatal slices at concentrations having no effect on ionotropic glutamate receptors (Schoepp & Conn, 1993) or glutamate uptake systems (Robinson et al, 1993). A previous study in hippocampal slices (Boss & Conn, 1992) revealed that this effect is stereoselective, since (IS,3R)-ACPD and (lS,3S)-ACPD but not (lR,3S)-ACPD are able to generate a PLD response.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Our results show that (lS,3R)-ACPD, a mGluR agonist acting on multiple subtypes, stimulates PLD activity in adult rat hippocampal, neocortical and striatal slices at concentrations having no effect on ionotropic glutamate receptors (Schoepp & Conn, 1993) or glutamate uptake systems (Robinson et al, 1993). A previous study in hippocampal slices (Boss & Conn, 1992) revealed that this effect is stereoselective, since (IS,3R)-ACPD and (lS,3S)-ACPD but not (lR,3S)-ACPD are able to generate a PLD response.…”
Section: Discussionmentioning
confidence: 87%
“…In evaluating the potencies of PLD agonists it should be taken into account that some of these agents (such as quisqualate, L-CCG-I or L-AP3) have been demonstrated to interact with sodium-dependent L-[3H]-glutamate uptake into synaptosomes (Robinson et al, 1993), and thus may be substrates for carriers reducing their concentration at the receptor level. In any case, these rank orders do not appear to correspond to that of any specific mGluR subtype and, in particular, the insensitivity to L-AP4 clearly rules out the possibility that PLD-coupled receptors might be members of the third group.…”
Section: Discussionmentioning
confidence: 99%
“…The glutamate uptake inhibitors THA, DHK, and aMG were used to characterize the pharmacological profile of the Y-79 glutamate transporter. Whereas THA has been shown to be a nonselective inhibitor of glutamate uptake in many preparations, including the human EAAT family (Arriza et al, 1994(Arriza et al, , 1997, aMG is a potent inhibitor of glutamate uptake in rat cerebellum, but not in the cortex (Robinson et al, 1993), and DHK is a relatively selective inhibitor of the EAAT2/ GLT-l transporter subtype (Pines et al, 1992). Preincubation of Y-79 cells with THA produced a concentration-dependent inhibition, with an IC 50 of 2.0 ±0.43 jiM.…”
Section: Discussionmentioning
confidence: 99%
“…34,35) The general pattern of structural selectivity of GluT, as set by the data obtained in rat cerebral cortex slices 19,26) was, however, confirmed in all major studies using synaptosomes or cultured cells. 97,98) In 1979, dihydrokainate (DHK) was shown to be a relatively specific, if not very potent, inhibitor of [ 3 H]L-glutamate uptake 99) and this pointed the way towards the preparation of similar, conformationally restricted structural analogues of glutamate or aspartate that would be more potent and could be used as highly specific probes for studies of GluT. Since the late 1980's, several such substrates or inhibitors of GluT have been synthesised (Fig.…”
Section: H]d-aspartate Compared To the Distribution Of Glast (Eaat1) mentioning
confidence: 99%
“…As pointed out earlier, there has been a wealth of information on the substrate specificity and structural requirements of GluT 19,26,34,[92][93][94][95][96][97][98][99][100][101]103,105,[107][108][109] even in relation to individual EAAT's 110,112,114,[179][180][181][182][183] yet this structure-activity data has not so far been satisfactorily matched with the protein architecture of the putative substrate-binding regions. Moreover, some of the EAAT's may form multimeric complexes 184) and most of them also act as chloride channels 185) ; for a review see ref.…”
Section: Unresolved Problems and Future Direc-tionsmentioning
confidence: 99%